Quality Parameters of 3D Print Products by the DMLS Method - Dvorak, Karel; Zarybnicka, Lucie; Dvorakova, Jana (Manufacturing Technology Journal, 2019)
Additive technologies are a dynamically evolving category of manufacturing methods for a wide range of industries, particularly engineering and related fields. Compared to traditional technologies based on chip machining, molding and casting, they offer new production options, particularly for complex shape components. At the same time, however, there are differences and limits that must be taken into account when designing functional machine parts. The important quality parameters of the products are in particular the dimensions and the quality of the surface. These factors are of fundamental importance for the subsequent assembly and function of a component in a plant assembly. They determine, together with the structural material properties, the usability of the component and the economic efficiency of the production in order to achieve the finished product with the minimum need for postprocessing the finished part. The submited text presents the results of the quality parameter research carried out on 3D print products made by the DMLS method, where the focus is put on the assessment of linear dimensions and the surface quality of samples from three selected materials and a combination of two print modifications. The measurement results are compared to generally valid standards and tabulated values to verify and eventually modify table values for use when designing a design solution with the use of 3D print products.
Keywords: Aditive Manufacturing; Digital Model; Dimensions; Surface quality; Roughness